PROGRAM PENDAMPINGAN PENULISAN ESAI OLEH ALUMNI DENGAN PENERIMA BEASISWA FULBRIGHT-INDONESIA - Tanasale, Inggrit Olivin (Universitas Pattimura, 2023)
The Fulbright Mentoring Program is a program that offers assistance to Fulbright scholarship recipients who wish to pursue Masters and Doctoral studies in the United States. This program was joined by the author as a Fulbright alumni with one of the Fulbright-Dikti scholarship recipient from August and September 2022. The mentorship program provides mentoring services in essay writing for applications in Masters and Doctoral programs at universities in the United States. In the program, correspondence is carried out between alumni as mentors and candidates as mentees. This program provides benefits to both parties because the mentor improves skills in providing feedback in essay writing and the mentee can revise and produce good quality essay writing